PERSEPSI PETANI TERHADAP PENTINGNYA PERAN PENYULUHAN PERKEBUNAN KARET (Hevea brasiliensis Muell Arg) DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Sariyem '; Roza Yulida; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research aims to (1)figure out the implementation system of rubber plantation extension, (2) farmers’ perception toward the importance of the role of extension in rubber plantation. Purposive Sampling method was the sampling technique that was used in this research which in accordance to the number of farmers that are actively involved in farmer group that consist of 45 farmers and 5 extension workers, Scale of Likert Summated Rating (LSR) was used as the tool of data analysis. The result showed the extension implementation activities in Gunung Toar Subdistrict Kuantan Singingi Regency have been going quite well if it is observed from the elements of extension that affecting it, that consists of agricultural extension workers; extension target; extension method; extension media; extenison material; extension period; extension site. Farmers’ perception toward the importance of the role of extension in rubber plantation in Gunung Toar Subdistrict Kuantan Singingi Regency was chategorized as “quite important” with the score of 2.80, it can be seen from the variable; (a) Education, information/innovation dissemination whichwere chategorized as “quite important” with the score of 3.17 and 2.68; (b) Facilitiation, Monitoring and evaluaton were chategorized as “less important” with the score of 2.53 and 2.00; (c) Consultation, Supervision/developmentwere included as “quite important” with the score of 3.15 and 3.29. Keywords: Perception, Farmers of Rubber, Extension Role, Rubber Plantation